“ANALISIS STUDI KELAYAKAN BISNIS PADA UMKM USAHA SEMUA SUKA FRIED CHICKEN (SSFC) DITINJAU DARI ASPEK STUDI KELAYAKAN BISNISâ€ - Putri Kumala Dewi Lubis; Anisa Fitria sinaga; Atika Atayarisah Lubis; Regita Amelia (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2025)
All Like Fried Chicken (SSFC) is a micro, small and medium enterprise (MSME) in the culinary sector that focuses on serving fried chicken at affordable prices aimed at the lower middle class. This research aims to analyze the business feasibility of the All Like Fried Chicken (SSFC) business by considering the main aspects in a business feasibility study, namely legal, environmental, market and marketing, technical and technological, management and human resources, as well as financial aspects. . The research method used is a qualitative method with a descriptive approach, where data is collected through observation, interviews and direct documentation in the field. Based on the analysis results, SSFC was declared feasible from a legal perspective because it had fulfilled all business licensing requirements. The environmental aspect shows SSFC's concern in managing waste efficiently, while the market and marketing aspects are supported by an affordable price strategy and active promotion on social media. From technical and technological aspects, strategic business locations and the use of simple but effective technology support business sustainability. In the management and human resources aspects, SSFC has implemented SOPs and employee training that maintain operational consistency. Overall, this research concludes that the Everyone Likes Fried Chicken (SSFC) business is worthy of being run and developed further, and has good prospects for business expansion in the future.